PENGARUH PESAN KAMPANYE #BELAJARJADIMINIMALIS TERHADAP PERILAKU SUSTAINABLE LIVING (Survei pada Followers Instagram @lyfewithless) - Meilly Joice Palentina Sirait (2024)
Lyfe With Less is an online community that promotes a minimalist lifestyle through the campaign message #BelajarJadiMinimalis as a form of environmentally conscious behavior. However, this campaign message has not been effective due to the onslaught of consumerism leading to increased online shopping activities, resulting in environmental pollution. This study aims to examine the extent of the influence of the #BelajarJadiMinimalis campaign message on sustainable living behavior among followers of the Instagram account @lyfewithless using the Theory of Planned Behavior (TPB) as the theoretical framework. The method employed is a quantitative research approach using an explanatory research design. Data collection involved conducting an online survey through the distribution of closed-ended questionnaires to 100 respondents selected from the followers of Instagram @lyfewithless, utilizing purposive sampling. The research findings indicate a significant and positive impact of the campaign message on sustainable living behavior, with the correlation test indicating a reasonably strong relationship. Thus, it is concluded that the #BelajarJadiMinimalis campaign message significantly influences the sustainable living behavior of the followers on Instagram @lyfewithless.